Cardiovascular Disease Mortality Among Breast Cancer Survivors. Issue 1 (January 2016) - Bradshaw, Patrick T.; Stevens, June; Khankari, Nikhil; Teitelbaum, Susan L.; Neugut, Alfred I.; Gammon, Marilie D.
Abstract : Background: Cardiovascular disease (CVD) is of increasing concern among breast cancer survivors. However, the burden of this comorbidity in this group relative to the general population, and its temporal pattern, remains unknown. Methods: We compared deaths due to CVD in a population-based sample of 1, 413 women with incident breast cancer diagnosed in 1996–1997, and 1, 411 age-matched women without breast cancer. Date and cause of death through December 31, 2009 were assessed through the national death index and covariate data was gathered through structured interviews and medical record abstraction. Hazard ratios (HR) and 95% confidence intervals were calculated using Cox regression for overall mortality (HR) and CVD-specific death (cause-specific HR). Subdistribution HRs for CVD death were estimated from the Fine-Gray model. Results: Risk of death was greater among breast cancer survivors compared with women without breast cancer (HR: 1.8 [1.5, 2.1]). An increase in CVD-related death among breast cancer survivors was evident only 7 years after diagnosis (years 0–7, cause-specific HR: 0.80 [0.53, 1.2], subdistribution HR: 0.59 [0.40, 0.87]); years 7+, cause-specific HR: 1.8 [1.3, 2.5], subdistribution HR: 1.9 [1.4, 2.7]; P interaction: 0.001). An increase in CVD-related mortality was observed among breast cancer survivors receiving chemotherapy. Conclusions: Breast cancer survivors are at greater risk for CVD-related mortality compared with women without breast cancer and this increase in risk is manifested approximately 7 years after diagnosis. Efforts should be made to identify risk factors and interventions that can be employed during this brief window to reduce the excess burden of CVD in this vulnerable population.